2007
DOI: 10.1007/s10668-007-9103-6
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural productivity and environmental insecurity in the Usangu plain, Tanzania: policy implications for sustainability of agriculture

Abstract: Sustainable agricultural development is a necessity for sustainable economic growth and social development in Africa. Sustainable agriculture largely depends on how effective natural and environmental resources are managed and utilized; it also depends on the security of continuous access to such resources. This research was aimed to look into trends in agricultural productivity, examine the persistence of the environmental insecurity, analyze the relationship between the two, and explore their links to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
(13 reference statements)
1
15
0
Order By: Relevance
“…In the northern parts of the country frequently hit by drought, water stress reduces yields especially for production under an extensive farming system [20].…”
Section: Water Constraintmentioning
confidence: 99%
“…In the northern parts of the country frequently hit by drought, water stress reduces yields especially for production under an extensive farming system [20].…”
Section: Water Constraintmentioning
confidence: 99%
“…These negative trends also occur in the RC system (Section A.5). One causing factor is likely to be the strong decline in fertilizer use since 1990 due to market liberalization and consequent price increases (Malley et al 2009;Skarstein 2005). Based on our own analysis of national FAOSTAT fertilizer consumption data, most other MM countries show positive trends in this time period, although more recent declines occur (e.g.…”
Section: A7 Maize Mixed (Mm)mentioning
confidence: 99%
“…Our CRU analysis does not show a decrease in rainfall for 1982-2006, although a significant warming trend is observed, which may imply higher evaporation losses and hence drier conditions. Other potential drivers are rapid population growth and soil fertility decline (Enfors and Gordon 2007;Malley et al 2009) causing an increased pressure on available natural resources. These processes result in declining maize surpluses thus threatening national food security (Dixon et al 2001).…”
Section: A7 Maize Mixed (Mm)mentioning
confidence: 99%
“…In Tanzania, linkages of the impacts of climate change caused by environmental changes on rural livelihoods are increasingly evident (Madulu 2003;Malley et al 2007aMalley et al , 2007bMalley et al , 2008aMalley et al , 2008b. Madulu (2003) observed a strong link of poverty to change in climate.…”
Section: Introductionmentioning
confidence: 99%
“…Madulu (2003) observed a strong link of poverty to change in climate. Malley et al (2007a) analysed the semi-arid Usangu plain, SW Tanzania and found a link between increasing climate variability and increasing water stress that has caused a decline in land productive quality and a notable decline in agricultural productivity. Other effects of climate variability were increases in rural conflicts over land and water resources (Malley et al 2008b), a decline in wildlife biodiversity and energy generation capacity in Mtera (Malley et al 2007b) and health risks due to increased scarcity of water for domestic needs (Malley et al 2008a).…”
Section: Introductionmentioning
confidence: 99%